Pengaruh Pengalaman Berwirausaha dan Pengembangan Kemampuan Sumber Daya Manusia Terhadap Kinerja Karyawan Menjalankan Usaha pada Pedagang Kuliner di Pajak USU Jalan Jamin Ginting Kota Medan - Surya, Dimas; Siregar, Dahrul; Siregar, Yamin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research seeks to ascertain the effect of Entrepreneurial Experience and the development of human resource capabilities on employee performance running a business on culinary traders at USU Tax Street Jamin Ginting Medan City. This study was put together utilizing quantitative techniques with causal associative research. The study's population consists of employees who run a business at culinary traders at the USU Tax Jalan Jamin Ginting Medan City and according to the Slovin formula's computation, it is determined that the study's sample consisted of 71 respondents with the use of purposive sampling techniques to obtain accurate and representative information from the population. This study's data collection method made use of a questionnaire media distributed directly using Gform. The results showed that partially entrepreneurial experience has a favorable and substantial impact on employee performance, partially the development of HR capabilities has a favorable and substantial impact on employee performance and simultaneously entrepreneurial experience and the development of HR capabilities have a favorable and substantial impact on employee performance running a business on culinary traders at USU Tax Jalan Jamin Ginting Medan City. In light of the test findings of the Coefficient of Determination (R2), it is found that the Adjusted R Square value is 0.545 (54.5%) which describes that the value of the variance owned by employee performance from the entrepreneurial experience variable and the development of HR capabilities is 54.5% With the rest of 45.5% is impacted by additional variables or aspects that this study did not look at or explain.